Implementation Model of Islamic Religious Education Curriculum at Various Levels of Education - Rusman Rusman (STAIFAS-Press, 2023)
The purpose of this research is to find out the implementation of the Islamic Religious Education curriculum policy at various levels of education. the research method used is library research with a leatherative method. Data sources come from books. The data collection technique used is documentation while the data analysis technique consists of four stages, namely data collection, data reduction, data presentation, and inference. The results of the research found that the Islamic Religious Education (PAI) Curriculum at various levels of education (Schools, Madrasahs and Pesantren) consists of several aspects, namely aspects of the Qur'an-Hadith, faith or aqidah, morals, fiqh and aspects of tarikh (Islamic history).